Guide rail and manufacturing method thereof

By controlling the composition and cooling rate of the guide rail steel, an excellent pearlitic structure is formed, solving the problem of insufficient resistance to breakage in the guide rail web and achieving efficient manufacturing and long-life guide rails.

CN120898013APending Publication Date: 2025-11-04JFE STEEL CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480020077.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-24
Filing Date
2024-01-16
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

In the existing technology, the bracing resistance of the guide rail body is insufficient, which leads to an increased replacement frequency. In addition, the manufacturing process is inefficient or the composition is poorly controlled, making it difficult to simultaneously meet the requirements of wear resistance and crack propagation inhibition.

Method used

By controlling the composition of the guide rail steel, ensuring that the contents of C, Si, Mn, and Cr are within a specific range, and cooling the guide rail web at a certain speed after hot rolling, the average value and deviation of Vickers hardness are controlled, thus forming an excellent pearlitic structure.

Benefits of technology

This improved the resistance to breakage of the guide rail web, extended the service life of the guide rail, reduced the occurrence of railway accidents, and achieved a highly efficient manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120898013A_ABST
    Figure CN120898013A_ABST
Patent Text Reader

Abstract

Provided is a guide rail having excellent resistance to breakage in the abdomen of the guide rail. A guide rail having a component composition containing 0.70 to 1.20 mass% of C, 0.10 to 1.20 mass% of Si, 0.10 to 1.80 mass% of Mn, 0.035 mass% or less of P, 0.020 mass% or less of S, and 0.05 to 1.80 mass% of Cr, with the remainder comprising Fe and unavoidable impurities, when the Vickers hardness at a position 0.5 mm deep from the surface of the web of the guide rail is measured in a range of + / -17.5 mm above and below the center position of the height of the guide rail, the average value of the Vickers hardness is Hv280 or more, and the standard deviation is 5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a rail and a manufacturing method thereof. BACKGROUND

[0002] For a heavy axle railway mainly for ore transportation and the like, the load received by the axle of a freight car is much higher than that of a passenger car, and the use environment of the rail is also severe. Therefore, from the viewpoint of valuing wear resistance, the rail used has mainly used a steel having a pearlite structure.

[0003] In recent years, in order to increase the efficiency of railway transportation, the loading weight of a freight car is further increased. In addition, due to the increase in transportation capacity, the number of wheels passing through the rail is also increased.

[0004] The web of the outer rail laid in the curve section is repeatedly subjected to bending stress by the passing of the wheels. As a result, there is a tendency that the frequency of replacement of the rail due to web breakage is increasing year by year. Therefore, there is a demand for a rail steel that improves the web breakage resistance of the rail web.

[0005] In the above background, various studies focusing on the rail web have been conducted. For example, Patent Literature 1 discloses a method in which the web is quenched at a cooling rate of 15°C / sec or more, then cooled to a temperature of 250 to 450°C to stop cooling, and when the bainite transformation reaches 30% or more, cooled to the Ms point or less to obtain a martensite structure, so that the web becomes a high-toughness tempered martensite structure.

[0006] Patent Literature 2 discloses a method of manufacturing a rail in which a compressed residual stress is imparted by cooling from the head to the upper neck or the web with a high-pressure gas or a water-containing gas, thereby improving the fracture resistance of the rail fastening portion.

[0007] Patent Literature 3 discloses a rail having a prescribed composition, in which 90 area% or more of the metal structure of the cross section of the rail stem portion is a pearlite structure, the minimum value of the hardness of the cross section of the rail stem portion is Hv300 or more, and the difference between the maximum value and the minimum value of the hardness of the cross section of the rail stem portion is Hv40 or less, and the rail has excellent fatigue damage resistance of the web.

[0008] PRIOR ART DOCUMENTS

[0009] PATENT LITERATURE

[0010] Patent Literature 1: Japanese Patent Application Laid-Open No. 62-99438

[0011] Patent Literature 2: Japanese Patent Application Laid-Open No. 59-47326

[0012] Patent Literature 3: International Publication No. 2020 / 189232 SUMMARY

[0013] However, in the above-described prior art, there are still problems to be solved. The disclosed technology of Patent Document 1 requires maintaining the temperature until the beginning of the bainite transformation, and thus the production efficiency is low. In addition, the disclosed technology of Patent Document 2 does not necessarily obtain the desired crack propagation inhibition ability of the web because the most important thing is to obtain the wear resistance / fatigue damage resistance of the head, and depending on the manufacturing conditions, it is possible to generate a martensite structure having high crack sensitivity. Furthermore, for the technology described in Patent Document 3, depending on the combination of the composition and the manufacturing conditions, there are cases where the surface hardness deviates, and it is difficult to say that the fold damage resistance of the web is sufficient.

[0014] The present application has been made in order to advantageously solve the above-described problems, and aims to provide a guide rail having excellent fold damage resistance of the web, and a manufacturing method thereof.

[0015] The present inventors and others have made a guide rail in which the contents of C, Si, Mn, and Cr are changed, and have intensively investigated the hardness of the web of the guide rail and the three-point bending property. As a result, it has been found that by ensuring that the surface hardness of the web is a certain value or more, and strictly controlling the hardness deviation at the above-described position, excellent fold damage resistance can be obtained.

[0016] The present application is based on the above-described insight, and the gist of the present application is as follows.

[0017] [1] A guide rail having a composition consisting of: C: 0.70 to 1.20 mass%, Si: 0.10 to 1.20 mass%, Mn: 0.10 to 1.50 mass%, P: 0.035 mass% or less, S: 0.020 mass% or less, and Cr: 0.05 to 1.80 mass%, with the remainder consisting of Fe and unavoidable impurities.

[0018] When the Vickers hardness of a position 0.5 mm in depth from the surface of the web of the guide rail is measured for a range of ±17.5 mm above and below the central position of the guide rail height, the average value of the Vickers hardness is Hv280 or more, and the standard deviation is 5 or less.

[0019] [2] The guide rail according to [1], wherein the above-described composition further contains at least one selected from V: 0.30 mass% or less, Cu: 1.0 mass% or less, Ni: 1.0 mass% or less, Nb: 0.05 mass% or less, Mo: 2.0 mass% or less, Al: 0.07 mass% or less, W: 1.0 mass% or less, Co: 1.0 mass% or less, B: 0.005 mass% or less, Ti: 0.05 mass% or less, Sb: 0.05 mass% or less, Mg: 0.01 mass% or less, Ca: 0.02 mass% or less, and Sn: 0.05 mass% or less.

[0020] [3] A method for manufacturing a rail, the method for manufacturing a rail of [1] or [2],

[0021] In manufacturing the rail by hot-rolling the steel material having the composition described in [1] or [2], the cooling after the hot-rolling is performed in such a manner that the average cooling rate from the cooling start temperature of 750°C or higher to the cooling stop temperature of 450 to 600°C is 0.4 to 5.0°C / sec at each of the position of the rail height center, the position 20 mm above the rail height center, and the position 20 mm below the rail height center of the rail web, and the difference between the average cooling rates at the positions is 0.5°C / sec or less.

[0022] According to the present application, a rail having an excellent fatigue fracture resistance of a rail web and a method for manufacturing the same can be provided. The rail of the present application contributes to the high durability of a rail for a heavy axle load railway, the prevention of railway accidents, and is industrially useful. The method for manufacturing the rail of the present application can stably manufacture the rail of the present application and is industrially useful. BRIEF DESCRIPTION OF DRAWINGS

[0023] Figure 1 is a rail sectional view.

[0024] Figure 2 is a view showing the position of a test piece for Vickers hardness measurement taken from a rail web.

[0025] Figure 3 is a schematic view showing a cooling method for a rail web.

[0026] Figure 4 is a view showing the position of a test piece for a three-point bending test taken from a rail web.

[0027] Figure 5 is an explanatory view explaining the shape of a test piece for a three-point bending test of a rail web. DETAILED DESCRIPTION

[0028] <POSITIONS OF RAIL>

[0029] First, referring to the rail sectional view of Figure 1 , the designations of the respective portions of the rail of the present application will be explained. In the rail 1 shown in Figure 1 , 11 denotes a rail head portion, 12 denotes a rail web portion, and 13 denotes a rail foot portion. Hereinafter, the rail head portion, the rail web portion, and the rail foot portion are sometimes referred to as a head portion, a web portion, and a foot portion, respectively.

[0030] <COMPOSITION OF RAIL>

[0031] Next, the composition of the steel of the rail of the present application will be explained. In the following explanation, "%" means "mass %" unless otherwise specified.

[0032] C: 0.70 to 1.20%

[0033] C is an essential element for ensuring the strength of the pearlite structure, i.e., the folding resistance. When the C content is less than 0.70%, it is difficult to obtain excellent folding resistance. In addition, when the C content exceeds 1.20%, a large amount of pro-eutectoid cementite is generated at the austenite grain boundaries during cooling after hot rolling, resulting in a decrease in the folding resistance. Note that pro-eutectoid cementite also exists when the C content is 1.20% or less, but the amount generated is small, so the effect on the folding resistance is slight. From these viewpoints, the C content is in the range of 0.70 to 1.20%, preferably in the range of 0.70 to 0.89%, and more preferably in the range of 0.70 to 0.85%.

[0034] Si: 0.10 to 1.20%

[0035] Si is an element that contributes to strengthening the pearlite structure, i.e., improving the folding resistance, by increasing the pearlite equilibrium transformation temperature and making the lamellar spacing fine, in addition to the effect as a deoxidizer. From this viewpoint, the Si content needs to be 0.10% or more, but when it exceeds 1.20%, bainite and martensite structures are easily generated in the surface layer portion, so the hardness deviation is exacerbated, and as a result, the folding resistance decreases. In addition, the oxide of Si increases, so the weldability also deteriorates. From these viewpoints, the Si content is in the range of 0.10 to 1.20%, preferably in the range of 0.15 to 1.10%, and more preferably in the range of 0.20 to 1.00%.

[0036] Mn: 0.10 to 1.50%

[0037] Mn is an element that contributes to strengthening the pearlite structure, i.e., improving the folding resistance, by lowering the pearlite transformation temperature and making the lamellar spacing fine. When the Mn content is less than 0.10%, the effect is not sufficient. On the other hand, when the Mn content exceeds 1.50%, bainite and martensite structures are easily generated in the surface layer portion, so the hardness deviation is exacerbated, and as a result, the folding resistance decreases. In addition, Mn has the effect of moving the eutectoid point to the low-C side, so excessive addition promotes the generation of pro-eutectoid cementite, resulting in a decrease in the folding resistance. From these viewpoints, the Mn content is in the range of 0.10 to 1.50%, preferably in the range of 0.20 to 1.40%, and more preferably in the range of 0.30 to 1.30%.

[0038] P: 0.035% or less

[0039] When P is contained in an amount exceeding 0.035%, the folding endurance and ductility are deteriorated. Therefore, the P content is 0.035% or less, preferably 0.020% or less. The lower limit of the P content is not particularly limited and can be 0%, but it is a common practice in industry to contain more than 0%, and excessive reduction of the P content results in an increase in refining cost. From the viewpoint of economy, it is preferable to make the P content 0.001% or more.

[0040] S: 0.020% or less

[0041] S is an element that exists in steel mainly in the form of A-type inclusions, but when the S content exceeds 0.020%, the amount of the inclusions increases significantly, and coarse inclusions are generated, thus causing deterioration of the folding endurance and ductility. Therefore, the S content is 0.020% or less, preferably 0.015% or less, and more preferably 0.010% or less. The lower limit of the S content is not particularly limited and can be 0%, but it is a common practice in industry to contain more than 0%, and excessive reduction of the S content results in an increase in refining cost. From the viewpoint of economy, it is preferable to make the S content 0.0005% or more.

[0042] Cr: 0.05 to 1.80%

[0043] Cr is an element that contributes to strengthening of the pearlite structure, i.e., improvement of the folding endurance, by increasing the pearlite equilibrium phase transformation temperature and making the lamellar spacing fine. When the Cr content is less than 0.05%, sufficient effects are not obtained. On the other hand, when the Cr content exceeds 1.80%, the hardenability of the steel becomes high, and bainite and martensite structures are easily generated in the surface layer, thus exacerbating the hardness deviation, with the result that the folding endurance is reduced. From these viewpoints, the Cr content is in the range of 0.05 to 1.80%, preferably in the range of 0.10 to 1.60%, and more preferably in the range of 0.15 to 1.40%.

[0044] The composition of the rail used in the present application can arbitrarily contain, in addition to the above-mentioned essential components, at least one selected from the following.

[0045] V: 0.30 mass% or less, Cu: 1.0 mass% or less, Ni: 1.0 mass% or less, Nb: 0.05 mass% or less, Mo: 2.0 mass% or less, Al: 0.07 mass% or less, W: 1.0 mass% or less, Co: 1.0 mass% or less, B: 0.005 mass% or less, Ti: 0.05 mass%, Sb: 0.05 mass% or less, Mg: 0.01 mass% or less, Ca: 0.02 mass% or less, and Sn: 0.05 mass% or less.

[0046] Hereinafter, the reasons for the above-mentioned arbitrary elements are described.

[0047] V: 0.30% or less

[0048] V is an element that forms a carbonitride in the steel and precipitates in the matrix to improve the resistance to breakage. When the V content exceeds 0.30%, the alloy cost, i.e., the manufacturing cost of the rail, increases in addition to the deterioration of the resistance to breakage and ductility. From these viewpoints, when the composition contains V, the V content is preferably capped at 0.30%. From the viewpoint of exhibiting the effect of improving the resistance to breakage, the V content is preferably 0.001% or more. The more preferable range of the V content is the range of 0.001 to 0.15%.

[0049] Cu: 1.0% or less

[0050] Cu is an element that enables further high strength of the steel through solid solution strengthening, like Cr. When the Cu content exceeds 1.0%, Cu cracking easily occurs, so when the composition contains Cu, the Cu content is preferably 1.0% or less. The more preferable range of the Cu content is the range of 0.001 to 0.5%.

[0051] Ni: 1.0% or less

[0052] Ni is an element that enables high strength of the steel without deteriorating the ductility. In addition, Cu cracking can be suppressed by complex addition with Cu, so when the composition contains Cu, it is also preferable to contain Ni. However, when the Ni content exceeds 1.0%, the hardenability of the steel further improves, the amount of martensite and bainite generated increases, and the resistance to breakage decreases. From these viewpoints, when the composition contains Ni, the Ni content is preferably 1.0% or less. The more preferable range of the Ni content is the range of 0.001 to 0.5%.

[0053] Nb: 0.05% or less

[0054] Nb is an element that, in hot rolling for forming the rail and after the hot rolling, combines with C in the steel to precipitate in the form of carbide, effectively acts on the refinement of the pearlite nodule size, and as a result, greatly improves the resistance to breakage, the resistance to wear, the resistance to fatigue damage, the ductility, and significantly contributes to the long life of the rail. However, even if the Nb content exceeds 0.05%, the improvement effect of each characteristic saturates, and an effect matching the increased content is not obtained. From these viewpoints, when the composition contains Nb, the upper limit of the Nb content is preferably 0.05%. From the viewpoint of obtaining a sufficient effect with respect to the long life of the rail, the Nb content is preferably 0.001% or more. The more preferable range of the Nb content is the range of 0.001 to 0.03%.

[0055] Mo: 2.0% or less

[0056] Mo is an element capable of achieving further high strength of the steel by solid solution strengthening. In addition, Mo has an effect of moving the eutectoid point to the high C side, and thus has an effect of suppressing the generation of proeutectoid cementite. However, when the Mo content exceeds 2.0%, the amount of bainite generated in the steel increases, and the bendability decreases. From these viewpoints, when the composition contains Mo, the Mo content is preferably 2.0% or less. From the viewpoint of high strength, the Mo content is preferably 0.001% or more. A more preferable range of the Mo content is 0.001 to 1.0%.

[0057] Al: 0.07% or less

[0058] Al is an element capable of being added as a deoxidizer. When the Al content exceeds 0.07%, oxide inclusions are generated in large amounts in the steel due to the high affinity of Al with oxygen, and as a result, the bendability and ductility of the steel decrease. Therefore, when the composition contains Al, the Al content is preferably 0.07% or less. The lower limit of the Al content is not particularly limited, but in order to deoxidize, it is preferably 0.001% or more. A more preferable range of the Al content is 0.001 to 0.03%.

[0059] W: 1.0% or less

[0060] W is an element that precipitates in the form of carbide during hot rolling into a rail shape and after the hot rolling, and improves the strength and bendability of the rail by precipitation strengthening. When the W content exceeds 1.0%, martensite is generated in the steel, and as a result, the bendability decreases. From these aspects, when the composition contains W, the W content is preferably 1.0% or less. The lower limit of the W content is not particularly limited, but in order to exhibit the above-mentioned effects of improving the strength and bendability, it is preferably 0.001% or more. A more preferable range of the W content is 0.001 to 0.5%.

[0061] Co: 1.0% or less

[0062] Co is an element capable of achieving further high strength of the steel by increasing the pearlite equilibrium phase transformation temperature and making the lamellar spacing fine. In addition, Co also has an effect of suppressing the precipitation of proeutectoid cementite. When the Co content exceeds 1.0%, martensite is generated in the steel, and as a result, the bendability decreases. From these viewpoints, when the composition contains Co, the Co content is preferably 1.0% or less. The lower limit of the Co content is not particularly limited, but in order to achieve high strength, it is preferably 0.001% or more. A more preferable range of the Co content is 0.001 to 0.5%.

[0063] B: 0.005% or less

[0064] B is an element which precipitates in the form of nitride in the steel during and after hot rolling to be shaped into a rail shape, and improves the strength and the resistance to breakage of the steel by precipitation strengthening. When the content of B exceeds 0.005%, martensite is generated, which results in a decrease in the resistance to breakage. From these viewpoints, when the composition contains B, the content of B is preferably 0.005% or less. The lower limit of the content of B is not particularly limited, but in order to exhibit the above-mentioned effects of improving the strength and the resistance to breakage, it is preferably 0.001% or more. More preferably, the content of B is in the range of 0.001 to 0.003%.

[0065] Ti: 0.05% or less

[0066] Ti is an element which precipitates in the form of carbide, nitride or carbonitride in the steel during and after hot rolling to be shaped into a rail shape, and improves the strength and the resistance to breakage of the steel by precipitation strengthening. When the content of Ti exceeds 0.05%, coarse carbide, nitride or carbonitride is generated, which results in a decrease in the resistance to breakage. From these viewpoints, when the composition contains Ti, the content of Ti is preferably 0.05% or less. The lower limit of the content of Ti is not particularly limited, but in order to exhibit the above-mentioned effects of improving the strength and the resistance to breakage, it is preferably 0.001% or more. More preferably, the content of Ti is in the range of 0.001 to 0.03%.

[0067] Sb: 0.05% or less

[0068] Sb is an element which has a remarkable effect of preventing decarburization of the steel during reheating of the rail billet using a reheating furnace before hot rolling. When the content of Sb exceeds 0.05%, adverse effects on the resistance to breakage and the toughness are caused, and therefore when the composition contains Sb, the content of Sb is preferably 0.05% or less. The lower limit of the content of Sb is not particularly limited, but in order to exhibit the effect of reducing the decarburized layer, it is preferably 0.001% or more. More preferably, the content of Sb is in the range of 0.001 to 0.03%.

[0069] Mg: 0.01% or less

[0070] Mg is an element for precipitating MgO by combining with oxygen to achieve further high strength. When the content of Mg exceeds 0.01%, adverse effects on the resistance to breakage and the toughness of the steel are caused due to an increase in MgO, and therefore when the composition contains Mg, the content of Mg is preferably 0.01% or less. The lower limit of the content of Mg is not particularly limited, but in order to exhibit the above-mentioned effects of improving the strength, it is preferably 0.001% or more. More preferably, the content of Mg is in the range of 0.001 to 0.005%.

[0071] Ca: 0.02% or less

[0072] Ca is an element for precipitating CaO in combination with oxygen to achieve further high strength. When the Ca content exceeds 0.02%, the steel's folding resistance and toughness are adversely affected due to the increase in CaO, and therefore, when the composition contains Ca, the Ca content is preferably 0.02% or less. The lower limit of the Ca content is not particularly limited, but in order to exhibit the above-mentioned effect of increasing strength, it is preferably 0.001% or more. A more preferable range of the Ca content is 0.001 to 0.01%.

[0073] Sn: 0.05% or less

[0074] Sn is an element that has a significant effect of preventing decarburization of the steel during reheating of the rail steel billet using a reheating furnace before hot rolling. When the Sn content exceeds 0.05%, the steel's ductility and toughness are adversely affected, and therefore, when the composition contains Sn, the Sn content is preferably 0.05% or less. The lower limit of the Sn content is not particularly limited, but in order to exhibit the effect of reducing the decarburized layer, it is preferably 0.001% or more. A more preferable range of the Sn content is 0.001 to 0.01%.

[0075] In the composition of the steel of the rail of the present application, the remaining portion of the above-mentioned essential components and optional components is composed of Fe and unavoidable impurities. Here, as the unavoidable impurities, N, O, etc. can be mentioned, and N can be allowed up to 0.008%, and O can be allowed up to 0.004%. It should be noted that depending on the conditions of the raw material, materials, manufacturing equipment, etc., impurities other than N and O can be unavoidably mixed into the steel. As the raw material, iron ore, reduced iron, scrap, etc. can be mentioned. As long as it is within a range that does not hinder the object of the present application, the mixing of the above-mentioned impurities is allowed. As the impurities other than N and O, Pb, Zr, Bi, Zn, Se, As, Te, Tl, Cd, Hf, Ag, Hg, Ga, Ge, REM, etc. can be mentioned.

[0076] < Microstructure of the rail >

[0077] The rail of the present application is a pearlite system rail, and the microstructure of the rail is 95% or more of pearlite in terms of area ratio. If the remaining structure other than the pearlite is 5% or less in terms of total area ratio, it does not greatly affect the fatigue crack propagation resistance characteristics, and therefore, it is allowed. As the remaining structure, for example, ferrite, proeutectoid cementite, bainite, and martensite can be mentioned.

[0078] < Vickers hardness >

[0079] In the present application, it is not enough that only the composition of the components satisfies the above range, and in order to obtain excellent folding damage resistance of the web, it is important that for the web, the Vickers hardness Hv at a position 0.5 mm from the surface of the web at the web height central position in a range of 17.5 mm above and below (a range of 35 mm in total) is controlled in a prescribed range. That is, the average value of the Vickers hardness of the above position is made 280 or more, and the standard deviation thereof is made 5 or less. From the viewpoint of stably obtaining the effect of improving the folding damage resistance, it is preferable that the average Vickers hardness of the above position be Hv 300 or more, and the standard deviation thereof be 4 or less.

[0080] Figure 2 In the present application, the web height is represented by the length A from the bottom surface of the foot portion to the top portion of the head, and the web height central position is the central position (A / 2 position) of the web height A. The range of 17.5 mm above and below the web height central position (a range of 35 mm in total) is located in the region indicated by the diagonal line. Figure 2 The Vickers hardness of the present application can be measured, for example, at a pressing load of 98 N at a position 0.5 mm in the depth direction from the surface of the web at the web height central position in a range of 17.5 mm above and below (a range of 35 mm in total), at an interval of 1 mm from the upper portion of the web toward the lower portion.

[0081] It should be noted that the reason why the hardness of the range of 17.5 mm above and below the web height central position (a range of 35 mm in total) is made the prescribed range is as follows.

[0082] As described above, repeated "bending stress" is applied to the web of the outer rail of the curve section. On the other hand, in a range of 17.5 mm above and below the web height central position of the web, a roll mark or an indentation is imparted. The present inventors have found that when the "bending stress" is applied, a part of the roll mark or the indentation becomes a stress concentration source, and folding damage occurs from the part. The present application is based on this insight, and for the web, the hardness of the range of 17.5 mm above and below the web height central position is controlled in a prescribed range.

[0083] Thus, in addition to the strengthening of the pearlite structure of the web, by strictly controlling the hardness deviation of the surface layer portion of the web, stress concentration in the locally softened portion can be suppressed, and the folding damage resistance of the web is greatly improved. The excellent folding damage resistance of the web is a characteristic generally required for the web, and is effective for the high durability of the web used in, for example, the straight section, the web in which a roll mark or an indentation is not imparted to the web, and the prevention of railway accidents.

[0084] <Shape of the rail>

[0085] The shape of the rail of the present application is not particularly limited, and can be the shape of a rail described in JIS E 1101:2001, BS EN 13674-1:2011, American Railway Engineering and Maintenance-of-Way Association (AREMA), or the like.

[0086] <Manufacturing method of rail>

[0087] A manufacturing method of the rail of the present application will be described. The rail of the present application can be manufactured by sequentially applying the following processes to a steel blank having the above-described composition.

[0088] The steel blank used as the rail blank has the above-described composition of the rail, and can be manufactured by an arbitrary method. It is generally preferable to manufacture the above-described steel blank by casting, particularly continuous casting.

[0089] (1) Hot rolling

[0090] The steel blank can be heated and then hot-rolled to form the shape of the rail.

[0091] (Heating temperature)

[0092] In the heating of the steel blank performed before the hot rolling, the heating temperature is preferably 1350°C or lower. When the heating temperature exceeds 1350°C, the steel blank is partially melted due to excessive heating, and there is a risk that a defect is generated inside the rail. On the other hand, the lower limit of the heating temperature is not particularly limited, but in order to reduce the deformation resistance at the time of rolling, it is preferable to be 1150°C or higher.

[0093] (Rolling end temperature)

[0094] The rolling end temperature of the hot rolling is preferably 850°C or higher. When the rolling end temperature is lower than 850°C, rolling is performed in the low-temperature region of austenite, and processing strain is introduced to the austenite grains, and thus the hardness of the pearlite structure generated by accelerated cooling easily deviates. Therefore, the rolling end temperature is preferably 850°C or higher. The upper limit of the rolling end temperature is not particularly limited, but if the original austenite grain size is extremely coarse, the folding resistance and toughness decrease, and thus it is preferable to be 1050°C or lower. Here, the rolling end temperature is the surface temperature of the central portion of the web of the rail on the side of the final rolling mill entrance, and can be measured with a radiation thermometer.

[0095] The other conditions of the hot rolling are not particularly limited.

[0096] (2) Accelerated cooling

[0097] By performing cooling after hot rolling, a rail can be obtained. In the cooling, the web portion of the rail is acceleratedly cooled. At this time, the average cooling speed from a cooling start temperature of 750°C or higher to a cooling stop temperature of 450 to 650°C is controlled to be 0.4 to 5.0°C / sec at each of a rail height center position (A / 2 position), a position 20 mm above the rail height center position (upper 20 mm position), and a position 20 mm below the rail height center position (lower 20 mm position) when the rail height is set to A, and the difference between the average cooling speeds of the three positions is 0.5°C / sec or less.

[0098] The method of accelerated cooling is not particularly limited, and can be performed by cooling using an in-line heat treatment apparatus, for example. The cooling medium is not particularly limited, and one or more selected from air, water spray, mist, and the like can be used, but air is preferably used.

[0099] In this accelerated cooling, when any one of the average cooling speeds at the rail height center position (A / 2 position), the position 20 mm above and below the rail height center position (upper 20 mm position and lower 20 mm position) is less than 0.4°C / sec, pro-eutectoid cementite is easily generated in addition to the thickening of the lamellar spacing of the surface layer of the web portion, and thus the folding damage resistance is reduced. In addition, the cooling time in the low temperature region increases, and thus there is a risk that the productivity is reduced and the manufacturing cost of the rail is increased. Therefore, the average cooling speeds at the above three positions are each 0.4°C / sec or more, and are preferably 1.0°C / sec or more. On the other hand, when any one of the average cooling speeds at the above three positions exceeds 5.0°C / sec, bainite and martensite structures are generated, and the folding damage resistance is reduced. Therefore, the average cooling speeds in the above range are each 5.0°C / sec or less, and are preferably 4.0°C / sec or less.

[0100] Further, when the difference between the average cooling speeds at the above three positions exceeds 0.5°C / sec, the hardness deviation of the surface layer of the web portion of the rail becomes large, and thus stress concentration is easily generated at the locally softened portion when a bending stress is applied, and the folding damage resistance is reduced. Therefore, the difference between the average cooling speeds at the above three positions is 0.5°C / sec or less, and is preferably 0.3°C / sec or less. The difference between the average cooling speeds at the three positions is the difference between the largest average cooling speed and the smallest average cooling speed among the average cooling speeds at the three positions.

[0101] Here, the control of the average cooling speed at the central position of the rail height (A / 2 position), the upper 20 mm position, and the lower 20 mm position will be described. With respect to the A / 2 position, the upper side and the lower side of the A / 2 position are easily affected by the radiant heat and the heat conduction from the rail head and the rail foot, respectively, in terms of the inflow of heat. It is presumed that if the average cooling speed at the A / 2 position, the upper 20 mm position, and the lower 20 mm position is controlled within an appropriate range (0.4 to 5.0°C / sec), and the difference in the average cooling speed at the three positions is controlled within a certain range (within 0.5°C / sec), the average cooling speed within the range of 20 mm above and below the A / 2 position (within the range of 40 mm in total) is appropriate and uniform.

[0102] By appropriately intensifying the accelerated cooling of the upper side of the A / 2 position and the lower side of the A / 2 position with respect to the A / 2 position, the difference in the average cooling speed at the above three positions can be stably within 0.5°C / sec.

[0103] For example, the nozzles can be provided in three stages in the height direction so as to directly irradiate the A / 2 position, the upper side of the A / 2 position, and the lower side of the A / 2 position, respectively, and the injection amount, the kind of the cooling medium at the three positions can be changed according to the temperature and the shape of the rail. For example, as shown in FIG. 6, the air nozzles can be provided in three stages so that the injection amount at the upper 20 mm position is the largest, the injection amount at the lower 20 mm position is the second largest, and the injection amount at the A / 2 position is the smallest. Figure 3

[0104] The temperature at which the average cooling speed is determined in the accelerated cooling is represented by the surface temperature at the A / 2 position, the upper 20 mm position, and the lower 20 mm position. They can be measured with a radiation thermometer. Here, the cooling start temperature is the temperature obtained by measuring the surface temperature of the rail web at the start of the accelerated cooling with a radiation thermometer, and the cooling stop temperature is the temperature obtained by measuring the surface temperature of the rail web after the stop of the accelerated cooling (before the reheating) with a radiation thermometer.

[0105] In the manufacturing method of the present application, it is important to perform the cooling after the hot rolling in such a manner that the surface temperature of the rail web satisfies the above condition, and if the condition is satisfied, the cooling method of the other portions of the rail (the rail head, the rail foot, etc.) is not particularly limited. The rail head and the rail foot can be naturally cooled, or the accelerated cooling can be performed.

[0106] (3) Others

[0107] The cooled rail material can be subjected to a known treatment, and for example, the cold roll straightening can be performed.

[0108] Example

[0109] ​The present application will be described more specifically below based on examples, but the present application is not limited to the examples, and can be appropriately changed within a range that can be adapted to the gist of the present application, and they are all included in the technical scope of the present application.

[0110] A 60-kg rail material according to JIS E1101 was manufactured by heating a steel billet material having the component composition shown in Table 1 under the conditions shown in Table 2, hot-rolling the steel billet material, and then accelerating cooling after the hot-rolling. The average cooling speed was obtained by converting the temperature change from the start of cooling to the stop of cooling by unit time (second) to the cooling speed (°C / second). Note that natural cooling was performed after the stop of cooling.

[0111] In the examples, for the acceleration cooling of the web of the rail, an air nozzle shown in Fig. 1 was used, and the amount of air injection was appropriately changed with the change in the cooling speed. In Test No. 34 of the comparative example, the acceleration cooling was performed using only one group of air nozzles provided at the A / 2 height among the air nozzles shown in Fig. 1. Figure 3 Figure 3

[0112] At the start and stop times of the acceleration cooling, a two-dimensional radiation thermometer capable of measuring the temperature distribution in the height direction of the web of the rail was used to measure the surface temperatures at the A / 2 position, the upper 20-mm position, and the lower 20-mm position, and the average cooling speeds at these three positions were calculated.

[0113]

[0114] [Table 2]

[0115]

[0116] ※Underline indicates out of the applicable range.

[0117] ※1 A indicates the rail height (A / 2 corresponds to the central position of the rail height).

[0118] ※2 Good: none of the two broke, Poor: at least one broke

[0119] The obtained rails were pearlite system rails. The Vickers hardness and the three-point bending properties of the web were evaluated for each rail. Table 2 shows the test results. Each evaluation item will be described in detail below.

[0120] <Vickers Hardness>

[0121] After cutting the front end portion of the rail after the completion of the acceleration cooling, a sample was taken from the web of the rail in a manner that included the surface of the web of the rail. Figure 2 ​​The portion within a 20mm range above and below the center position (position A / 2) of the guide rail height (a total range of 40mm) is used as the test piece for Vickers hardness testing. The test piece is embedded in resin and mirror-polished. For a range of 17.5mm above and below the center position (position A / 2) of the guide rail height (a total range of 35mm), a load of 98N is applied from the top of the guide rail towards the bottom at 1mm intervals, measuring the Vickers hardness at 36 points at a depth of 0.5mm from the surface of the guide rail web. Then, the average value and standard deviation are calculated from the obtained Vickers hardness values.

[0122] <Three-point bending characteristics>

[0123] like Figure 4 As shown, test pieces were taken from two locations on the guide rail's belly: 17.5 mm above and 17.5 mm below the center position (A / 2 position) of the guide rail height, in a manner encompassing the surface of the guide rail's belly. The shape of the test piece is as follows... Figure 5 As shown, the length L = 100 mm, width H = 10 mm, and thickness B = 10 mm. The surface corresponding to the guide rail's web surface in the test piece has a cut at the center L / 2 portion of the length L. The depth of the cut is N = 0.5 mm, the width of the cut is C = 1.0 mm, and the bottom of the cut has a radius of curvature R = 0.5 mm.

[0124] The test piece was placed with the cut facing down on a support with a distance of 50 mm between the support points and a radius of curvature of 17 mm. A pressure head with a radius of curvature of 16 mm was used to apply bending strain from the opposite side of the cut at an indentation speed of 0.1 mm / s. Tests were conducted on test pieces taken from these two locations. If neither fractured under a displacement of 1.0 mm, the guide rail web was evaluated as having excellent resistance to breakage.

[0125] As shown in Table 2, the test results of the guide rail materials in the inventive examples (Tests No. 1 to 39 in Table 2) show that the surface hardness deviation of the guide rail web is small, and all exhibit good three-point bending characteristics. On the other hand, comparative examples of guide rail materials whose composition does not meet the conditions of the present invention or whose manufacturing methods are outside the scope of the present invention (Tests No. 40 to 52 in Table 2) break before reaching the specified displacement in the three-point bending test.

[0126] Industrial availability

[0127] According to the present invention, a guide rail with excellent resistance to breakage in its web and a method for manufacturing the same can be provided. The guide rail of the present invention contributes to extending the service life of guide rails used in railways with heavy axle loads and preventing railway accidents, thus being industrially beneficial. The method for manufacturing the guide rail of the present invention allows for the stable production of the guide rail of the present invention, which is also industrially beneficial.

[0128] Symbol Explanation

[0129] 1 rail

[0130] 11 rail head (head)

[0131] 12 rail belly (belly)

[0132] 13 rail foot (foot)

Claims

1. A guide rail having the following composition: containing C: 0.70-1.20% by mass, Si: 0.10-1.20% by mass, Mn: 0.10-1.50% by mass, P: less than 0.035% by mass, S: less than 0.020% by mass and Cr: 0.05-1.80% by mass, the remainder being Fe and unavoidable impurities; When measuring the Vickers hardness at a depth of 0.5 mm from the surface of the guide rail web within a range of ±17.5 mm above and below the center position of the guide rail height, the average Vickers hardness is above Hv280 and the standard deviation is below 5.

2. The guide rail according to claim 1, wherein, The composition further comprises at least one of the following: V: less than 0.30% by mass, Cu: less than 1.0% by mass, Ni: less than 1.0% by mass, Nb: less than 0.05% by mass, Mo: less than 2.0% by mass, Al: less than 0.07% by mass, W: less than 1.0% by mass, Co: less than 1.0% by mass, B: less than 0.005% by mass, Ti: less than 0.05% by mass, Sb: less than 0.05% by mass, Mg: less than 0.01% by mass, Ca: less than 0.02% by mass, and Sn: less than 0.05% by mass.

3. A method for manufacturing a guide rail, which is the method for manufacturing a guide rail according to claim 1 or 2. When hot-rolling a steel billet having the composition described in claim 1 or 2 to manufacture a guide rail, the web of the guide rail is cooled after hot rolling in such a manner that the average cooling rate from a cooling start temperature of 750°C or higher to a cooling stop temperature of 450 to 650°C at each of the following locations—the center position of the guide rail height, the position 20 mm above the center position of the guide rail height, and the position 20 mm below the center position of the guide rail height—is 0.4 to 5.0°C / second, and the difference in the average cooling rate between each location is within 0.5°C / second.

Citation Information

Patent Citations

  • Production of rail having excellent resistance to edge rupture

    JP1984047326A

  • Wear-resistant high-efficiency rail having instable fracture propagation stopping capacity

    JP1987099438A

  • rail

    WO2020189232A1